Teaching functioning, disability and rehabilitation to first year medical students - Christoph Gutenbrunner; Birgit Kubat; Simon Kröhn; Hermann Haller; Jörg Schiller; Christoph Korallus; Christian Sturm (Medical Journals Sweden, 2021)
Background: Many patients have disabilities; it is therefore essential that medical education includes comprehensive teaching on disability and rehabilitation. In 2006 Hannover Medical School implemented an introductory course in the curriculum for medical students, on how to communicate with persons with disability and the need for rehabilitation. The course, entitled "Introduction to medicine", has the main goals of teaching the strategy and systematic approach of medicine to solving patients' problems. Methods: This paper describes the content, methods and outcomes of 1 of the 4 main themes of the "Introduction to medicine" course; the theme "Pain and disability", which is covered in the second week of the course. Results: Evaluation of the "Pain and disability" module found that students' ratings for the category "patient involvement" were very high (93%), whereas their ratings for the category "examination of student knowledge" were low. The overall rating of the module was "good" (10.8 out of 15 points), but not "very good". Conclusion: The concept of the "Pain and disability" module is feasible and successful, even though it is scheduled early in the first year of the curriculum and approximately 350 students participate. Factors related to this success are: a mixture of teaching knowledge, supporting students' understanding, and applying communication and physical examination skills.